Aquaporin 4-positive neuromyelitis optica spectrum disorder with meningoencephalitis-like onset: A case report - Bu, Yi; Liu, Heng; Qian, XuDong; Sun, Fan; Li, ChengBo; Han, Jingzhe (Frontiers in Immunology, 2022)
Neuromyelitis optica spectrum disease (NMOSD) is a debilitating autoimmune inflammatory demyelinating disease of the central nervous system. The relationship between harboring an infection and NMOSD is currently unclear and needs further investigation.In this article, we report a case of meningoencephalitis-like manifestations including fever, headache, neck resistance, seizures, and pleocytosis, accompanied by nausea and vomiting, in a patient with serum AQP4 antibody-positive area postrema syndrome (APS). In the presence of aseptic meningitis combined with clinical symptoms such as optic neuritis and myelitis, the possibility of NMOSD diagnosis can be considered. However, for patients with of unknown cause, especially combined with aseptic meningitis, a probable differential diagnosis of NMOSD is considered.